Long-term effects of creatine monohydrate on strength and power - Pearson, D. R.; Hamby, D. G.; Russel, W.; Harris, T. (The Journal of Strength and Conditioning Research, 1999)
The use of creatine monohydrate supplementation by athletes to increase strength and lean body mass has great anecdotal support. There has also been great interest in the use of lower doses of creatine monohydrate for extended periods during heavy resistance training. The purpose of this investigation was to document the long-term effects of creatine monohydrate supplementation on resistance-trained athletes. Sixteen collegiate football players were randomly separated into creatine monohydrate and placebo groups. Supplementation in capsule form consisted of 5 g/d of creatine monohydrate or placebo (no loading phase) throughout a 10-week supervised resistance training program. Pretesting and posttesting consisted of the following: weight; body fat estimation; 1 repetition maximum bench press, squat, and power clean; and Cybex testing. Results revealed the creatine monohydrate group was able to significantly increase measures of strength and power and increase body mass without a change in percent body fat, whereas the placebo group showed no significant changes. The results indicate that 10 weeks of creatine monohydrate supplementation while participating in a resistance training program significantly increases strength and power indices compared with placebo supplementation. These data also indicate that lower doses of creatine monohydrate may be ingested (5 g/d), without a short-term, large-dose loading phase (20 g/d), for an extended period to achieve significant performance enhancement.